Interpretation of the blade work profile - Kleshnev, V. (BioRow, 2018)
After force curve, the blade work profile is another important area of evaluation of rowing skill. Definitions of the blade work curve were given in RBN 2009/10 and 2015/08, and here we will give more insight about its interpretation.